Miejsce badań regionalnych w opisie dziejów polszczyzny = Regional Studies and the Study of the Development of the polish Language - Siuciak, Mirosława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is concerned with the study of the development of Polish in particular regions. This major aspect of historic-lingustic research refers to mainly the peripheries of the country, which for centuries remained outside the mainstream development of the Polish language. Special attention is given to Upper Silesia, a region which was ethnically and socially diverse and which until late Middle Ages stayed under foreign (Czech and German) cultural influences.
Keywords: historia języka; regionalność; badania śląskoznawcze; history of language; regionality; Upper Silesia studies